2014 International Joint Conference on Neural Networks (IJCNN) 2014
DOI: 10.1109/ijcnn.2014.6889615
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing slow eye movement for driver fatigue detection with machine learning approach

Abstract: Slow eye movement (SEM) regarded as a sign of onset of sleep is very significant for detecting driver fatigue, but its characteristics and detection algorithm have been rarely involved in the study of driver fatigue detection. In this study, some new features were extracted based on wavelet singularity analysis and statistics to detect SEMs. Six subjects participated in this simulated driving experiment, and for each subject, a more than 2 hours electro-oculogram (EOG) session was recorded. Each session was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The suggested methodology has a certain advantage over other DD detection methods described in Section II. Particularly, as compared to the methods, where the behavioral and psychological attributes are applied [6][7][8][9][10][11][12][13][14][15][16][17][18], the proposed approach does not require additional devices, such as cameras and neuroscan systems. Those devices increase the system cost [8], what in its turn is a potential resistance for system application in a commercial passenger vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested methodology has a certain advantage over other DD detection methods described in Section II. Particularly, as compared to the methods, where the behavioral and psychological attributes are applied [6][7][8][9][10][11][12][13][14][15][16][17][18], the proposed approach does not require additional devices, such as cameras and neuroscan systems. Those devices increase the system cost [8], what in its turn is a potential resistance for system application in a commercial passenger vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Fuzzy expert system combined eye and face regions for the DD level fatigue estimation in [14]. Different machine learning methods, in particular SVM, k-nearest neighbor (k-NN), and graph-regularized extreme learning machine were compared in [15]. The complex method designed in [7] connects the principle component analysis, the linear discriminate analysis, and SVM.…”
Section: Related Work and Problem Statementmentioning
confidence: 99%
“…The wavelet methods have been used in EOG features extraction [4], [10]. As the wavelet transform is sensitive to singularity, it obtains a better result than the derivative method in detecting blink and saccade.…”
Section: B Feature Extraction and Smoothingmentioning
confidence: 99%
“…There have been many studies on mental fatigue based on human physiological signal characteristics [7,8]. Previous studies have showed that human mental fatigue is associated with eye movement characteristics [9,10,11]. Di Stasi et al found that the saccadic eye movement parameters are sensitive indicators for human mental fatigue [12].…”
Section: Introductionmentioning
confidence: 99%